Abundance dynamics of mites (Acari) in the peatland of ‘Linie’ Nature Reserve, with particular reference to the Gamasida - Kaczmarek, Sławomir; Faleńczyk-Koziróg, Katarzyna; Marquardt, Tomasz (Biological Letters, 2012)
The research was conducted in ‘Linie’ Nature Reserve within the Lower Vistula Valley Land-scape Park in central Poland. We analysed the annual abundance dynamics of soil mites as well as changes in gamasid community parameters (abundance, age structure, species diversity). Density changes among the juvenile Gamasida greatly influenced the annual abundance dynamics of mites belonging to that order. Alternations in the abundance dynamics of Platyseius italicus and Zercon zelawaiensis were connected to the appearance of males as well as the density increase in juvenile specimens of those species.